DECENTRALIZATION, FISCAL CAPABILITY AND PUBLIC SPENDING EFFICIENCY - Hakim, Abdul; Sriyana, Jaka (Economic Journal of Emerging Markets, 2012)
Assigning autonomy to regency governments in Indonesia has failed to increase regency’s economies. While it increases regency government role in planning and initiating policies, its impact on economic development has been insignificant. This stems from the lack of institution’s capacity in organizing the bulk funds transfer from the central government which leads to inefficiency in resource allocation. This paper maps these regencies based on their fiscal dependency. This paper also applies Data Envelopment Analysis to identify the efficient and non efficient regencies in such a way that the non efficient regencies might use the efficient ones as the benchmark to increase their efficiency. Keywords: Autonomy, regency government, efficiency JEL classification numbers: H21, H53, H71, H72